Spin-Electromagnetics and Spin-Gravity vs Spin-Electromagnetics-Force and Spin-Gravity-Force (5th Force?) - Peng, Hui (European Journal of Applied Sciences, 2026)
The spin of electrons is studied (Spintronics) and applied to, for example, quantum computing. In this article, utilizing UMFT (Universal Mathematical Field Theory), we establish: (1) Spin-Electromagnetics (Spin-EM) from the Coulomb’s law and the spin of electric source. (2) Spin-gravity. Spin-EM and Spin-gravity predicts several new effects including the Spin-Lorentz-type force (including both Spin-Lorentz-type EM force and Spin-Lorentz-type gravity force), and Spin-Lagrangian-Lorentz-type force (including both Spin-Lagrangian-Lorentz-type EM force and Spin-Lagrangian-Lorentz-type gravity force). If experimentally confirmed, the Spin-force would be NEW FORCEs, 5th forces? The UMFT has been established and utilized to derive the Maxwell electromagnetics (Maxwell-EM) and Maxwell-type gravity (Gravito-EM). UMFT shows that mathematical identities lead to physical dualities, such as the duality between Maxwell-EM, Gravito-EM, Spin-EM, and Spin-gravity. The well-known-concepts, effects, and phenomena of Maxwell-EM may be converted respectively to Gravito-EM, Spin-EM, and Spin-gravity. The Maxwell-EM, Gravito-EM, Spin-EM, and Spin-gravity are all derived from UMFT and thus, they are dual to each other, and can be unified in the frame of UMFT.